Implementing Inquiry Learning Strategy to Improve Students’ Thinking Ability of SMPN 6 Gunungsitoli in 2023/2024 - Rini Suzwina Telaumbanua; Yaredi Waruwu; Elwin Piarawan Zebua; Afore Tahir Harefa (JELITA, 2024)
This research was motivated by initial observations which showed low student learning outcomes, which can be seen based on the average score on exam results, namely 60. The average score is still below the minimum completeness criteria (MCC) set by the school, namely 67, in English subjects. This shows that student learning outcomes in English learning are still low. This research aims to implement inquiry learning strategies in improving students' thinking skills and improving listening skills in English at SMP Negeri 6 Gunungsitoli. This research focuses on finding out the teaching methods used by teachers to improve students' thinking skills, implementation, assessment in learning with research results obtained through student observations in learning activities, questions to improve one of the students' competencies in listening skills, and the researcher's field notes. while carrying out research. The informants for this research were class 8, totaling 7 people. The method used in this research is Classroom Action Research (CAR). The results obtained from this research include: 1). Implementation of the learning process using the inquiry method. 2). Observation results showing improvement from the first cycle to the second cycle at the second meeting. 3). Implementation of listening tests for students makes students like learning English and through MCC. The average value presentation obtained is 90%. This shows an increase from cycles I and II student learning motivation through implementing the inquiry learning model in the When I was a child material with an average score of 90% in the very high category. The application of the inquiry learning model can increase students' activeness in learning, improve students' thinking abilities, and increase the completeness of learning outcomes.